Coconut shell-derived carbon materials via microwave pyrolysis and CO2 activation - Noor Ul Huda Altaf; Muhammad Ayyaz; Lorato Ayalkbet Tekle; Faizan Ahmad; Muhammad Yasin Naz; Yaning Zhang (Biomass and Bioenergy, 2027)

Flow instability characteristics of supercritical water in parallel vertical tubes under semicircular heating conditions - Attiq Ur Rehman; Hassaan Ahmad; Muhammad Faizan Ameer; Lubna Kanwal; Kashif Abbas; Dong Yang; Naseem Abbas (Annals of Nuclear Energy, 2026)

Mechanistic reprogramming by stem cell-derived extracellular vesicles: From cargo sorting to tissue regeneration - Muhammad Faizan Khan; Hina Wajid; Sumreen Begum (Tissue and Cell, 2026)

Engineering MOF-on-MOF heterostructure for enhanced adsorption-assisted photocatalytic decontamination of carbamazepine: Kinetics, thermodynamic and pathway study - Muhammad Fayaz; Raza Ullah; Muzamil Ahmad; Ikram Ullah; Muhammad Rafiq; Ali Ahmad; Nasim Ullah; Faizan Jamil; Latif Ur Rehman; Hammad Ali; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2026)

Advancing plastic waste-to-hydrogen: A cross-technology framework integrating eco-technoeconomic analysis, catalyst stability benchmarking and knowledge mapping - Usman Bello; Haruna Adamu; Muhammad Faizan; Abdul Aziz Jallow; Maryem Ourimi; Roa’a Alzoubi; Shafirah Samsuri; Abdul Gani Abdul Jameel; Mohammad Nahid Siddiqui (Journal of Environmental Chemical Engineering, 2026)

Development and Characterization of Proliposomes for Sustained Oral Delivery of the DPP-4 Inhibitor Vildagliptin - Shazia Ashraf; Asadullah Madni; Faizan Akram; Muhammad Farhan Hanif; Afifa Shafiq; Iqra Fatima Ayub (Journal of Pharmaceutical Innovation, 2026)

Anti-inflammatory properties of seaweed-derived bioactive compounds: Modulation of NF-κB, MAPK, and Nrf2/HO-1 pathways - Muhammad Faizan; Bomi Ryu; You-Jin Jeon; Lei Wang (Algal Research, 2026)

Retraction notice to “Environmentally responsive and anti-bugs textile finishes – Recent trends, challenges, and future perspectives” [Sci. Total Environ. 690 (2019) 667–682] - Shahzad Ali Shahid Chatha; Muhammad Asgher; Rabbia Asgher; Abdullah Ijaz Hussain; Yasir Iqbal; Syed Makhdoom Hussain; Muhammad Bilal; Faizan Saleem; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

Field portable Cr2O3 nanozyme based paper sensors for on-site screening of arsenic and cadmium in quality control of herbal products - Fatima Yaseen; Muhammad Faizan; Ali Turab Jafry; Awn Muhammad; Akhtar Hayat; Huma Ajab (Food Bioscience, 2026)

Protective effect of (−)-Loliode isolated from Sargassum horneri against particulate matter-induced skin damage via inhibiting pro-inflammatory cytokines and matrix metalloproteinases expression - Muhammad Faizan; Jun-Geon Je; Jimin Hyun; Kaiqiang Wang; Bomi Ryu; Lei Wang (Chemico-Biological Interactions, 2026)

Multifunctional Greenly Synthesized ZnFe2O4@ZnO Nanocomposites for Photodegradation of Azo Dyes and Antibacterial Applications: Effect of Radical Scavengers and Reaction Parameters - Muhammad Faizan; Muhammad Zahid Ishaque; Yasir Zaman; Abu Bakar Siddique; Muhammad Shahzad; Alia Arif; Hira Zaman (Water, Air, & Soil Pollution, 2026)

Structure-based immunopharmacological design of a multi-epitope vaccine candidate against Naegleria fowleri targeting TLR3: a pan-genomic and molecular dynamics approach - Rabia Faizan; Muhammad Naveed; Inmaculada Bellido Estevez; Hafiz Muzzammel Rehman; Ayesha Latif; Hafiz Muhammad Hammad; Abdul Rafay Khan; Seham O. Alsulami; Maha A. Aljumaa; Nantenaina Tombozara (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Insights into the Contortylenchus genitalicola (Tylenchida: Allantonematidae) parasitism in Monochamus alternatus (Coleoptera: Cerambycidae) in China - Lichao Wang; Huan Li; Yajing Song; Junwei Wang; Muhammad Faizan Latif; Chenning Zhang; Ming Xu; Min Li; Fengmao Chen (Journal of Invertebrate Pathology, 2026)

Sustainable valorization of date waste to renewable fuels and chemicals: Data-driven biorefinery analysis and techno-economic insight - Usman Bello; Haruna Adamu; Muhammad Faizan; Maryem Ourimi; Roa'a Alzoubi; Abdulaziz Jallow; Mohammad Nahid Siddiqui; Abdul Gani Abdul Jameel (Bioresource Technology Reports, 2026)

A machine learning framework for evaluating cyclic resistance of sands with non-plastic fines - Arslan Mushtaq; Muhammad Salman; Muhammad Noman; Muhammad Faizan; Afaq Ahmed (Innovative Infrastructure Solutions, 2026)

Efficacy of aripiprazole and valbenazine in the treatment of tourette syndrome: a systematic review and meta-analysis of randomized controlled trials - Muneeb Ahmad Muneer; Ume Habiba; Shajjia Shehzad; Washija Batool; Dawood Shah; Zain Shahzad; Muhammad Khizar Kirmani; Zohaib Hassan Siddiqui; Areeb Amjad; Ameer Hamza; Muhammad Faizan Khan; Fahad Siddique Butt; et al. (Acta Neurologica Belgica, 2026)

Electrospinning of food-grade polysaccharides and proteins: Materials, challenges, and applications - Khubaib Ali; Nadia Niaz; Faizan Ul Haq; Muhammad Waseem; Waqas Ashraf; Chen Guoxun; Mangang Wu (Carbohydrate Polymers, 2026)

CRISPR-Cas9 and next-generation gene editing strategies for therapeutic intervention of neurodegenerative pathways in Alzheimer’s disease: a state-of-the-art review - Muhammad Sohail Khan; Imran Zafar; Adil Jamal; Fayez Saeed Bahwerth; Samiullah Khan; Muhammad Faizan; Hanif Khan; Muhammad Noman; Kendrix Okeibunor; Ashfaq Ahmad; Muhammad Zain Ul Abedin (Acta Neurologica Belgica, 2026)

Electrodialysis for sustainable water desalination: Principles, applications, challenges, and future directions - Subhan Mahmood; Numan Mahmood; Muhammad Usman Liaquat; Faizan Ikhlaq; Hamza Shehzad; Shun Yao (Journal of Environmental Chemical Engineering, 2026)

pH-responsive pea protein-sodium alginate hydrogel beads for freshness monitoring in protein drinks: Structural and molecular insight - Khubaib Ali; Nadia Niaz; Fedrick C. Mgomi; Faizan Ul Haq; Waqas Ashraf; Muhammad Umair Khalid; Qingling Wang; Mangang Wu (Food Hydrocolloids, 2026)

Iodine availability in soil and accumulation by maize in limed and humic acid–amended soil fertilized with iodide and iodate - Asif Naeem; Muhammad Faizan Ilyas; Karl H. Mühling (Plant and Soil, 2026)

Miexianling: a novel dual-action pesticide for sustainable pine wilt disease management through integrated beetle and nematode control - Min Li; Guanyi Cheng; Ming Xu; Mengyao Wang; Yue Li; Jingeng Tang; Yinchu Chai; Kangquan Chen; Muhammad Faizan Latif; Ying Pei; Ting Yang; Yajing Song; et al. (Journal of Pest Science, 2026)

Classification of clay bricks using vision-based machine learning algorithms - Muhammad Faizan; Muhammad Salman; Muhammad Noman; Ali Akhtar; Afaq Ahmad; Matiullah Bakhtyar (Innovative Infrastructure Solutions, 2026)

Predicting fire resistance of reinforced concrete (RC) and concrete-filled steel tubular (CFST) columns through machine learning - Muhammad Noman; Muhammad Salman; Mati Ullah; Muhammad Faizan; Afaq Ahmed (Innovative Infrastructure Solutions, 2026)

Predicting axial load capacity of CFRP fire-damaged RC columns through DANN - Muhammad Noman; Muhammad Yaqub; Muhammad Salman; Muhammad Faizan; Shakouri Mahmoudabadi; Afaq Ahmad (Innovative Infrastructure Solutions, 2025)
This paper presents the results of a deep neural network (DNN) model predicting the axial load-carrying capacity of fire-damaged concrete square and rectangular reinforced concrete columns subsequently repaired using carbon fiber-reinforced polymer (CFRP) composites. An experimental database comprising 143 column specimen samples was collected from the literature. Thirteen parameters were noted, including Length of Columns (mm), Width of Columns (mm), Corner Radius (mm), Height of Column (mm), Initial Compressive Strength of Concrete (MPa), Initial Tensile Strength of Steel (MPa), Longitudinal Reinforcement Ratio (As/Ag, %), Temperature of Fire (°C), Fire Exposure Time (Minutes), Number of Layers of CFRP(Count), Thickness of CFRP (mm), and Tensile Elastic Modulus of CFRP (GPa). These parameters served as inputs for the model, with the final axial compressive strength of the CFRP-repaired column considered as the target/output. DNN models were calibrated for numerous numbers of neurons in the hidden layers to achieve optimization. The proposed DNN model demonstrated strong agreement with the experimental database, exhibiting an overall correlation factor (R) of 0.99946. The predicted outcomes of the proposed model closely align with the experimental findings, as evidenced by a thorough comparison with prior experimental investigations. Consequently, this model holds potential value for engineers seeking speedy assistance in repairing fire-damaged structures using CFRP composites.

Magnetic MOF-Based Immunosensing Strategy with Quantum Dot Labeling for Efficient Electro-chemiluminescent Detection of Alpha-fetoprotein - Mariyam Fatima; Muhammad Faizan; Iqra Jabeen; Muhammad Fiaz; Ansar Ali; Syed Kashif Ali; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Ibrahim Jafri; Abd-ElAziem Farouk (Journal of Fluorescence, 2025)

Modelling crop water demand under climate change: the case of Sardinia region - Muhammad Faizan Aslam; Sara Masia; Donatella Spano; Valentina Mereu; Marta Debolini; Richard L. Snyder; Andrea Borgo; Antonio Trabucco (Irrigation Science, 2025)

Circular economy strategies for converting waste plastics into surfactants - Muhammad Faizan; Abdulaziz Jallow; Mohammad Nahid Siddiqui (Journal of Environmental Chemical Engineering, 2025)

Asiatic black bear in Pakistan: a comprehensive review and conservation indications - Faizan Ahmad; Muhammad Rehan; Luciano Bosso; Muhammad Kabir (Mammalian Biology, 2025)
The Asiatic black bear ( Ursus thibetanus ) is considered as globally vulnerable, and its distribution in Pakistan has drastically decreased. The current knowledge around its biology and ecology is still poor. To provide crucial management and conservation recommendations for this threatened bear in Pakistan and in other areas in the world, we examined all the literature published from 1977 to 2024 on the two subspecies of U. thibetanus living in Pakistan, i.e., the Baluchistan black bear ( U. thibetanus gedrosianus ) and Himalayan black bear ( U. thibetanus laniger ). We found 59 papers on the Asiatic black bear, with the majority of the studies focusing on the bears’ existence, distribution, and human-bear conflicts, while only one study used a genetic approach. Questionnaire/interview surveys emerged as the most used method, followed by sign surveys, camera trapping, and visual observations. Most of the publications were focused on the Himalayan black bear in Azad Jammu and Kashmir and the Mansehra district (northern Pakistan), while few studies have been conducted in Balochistan since 1977 for the subspecies Baluchistan black bear. This underscores a significant geographic gap in research, particularly in the southern Pakistan regions that host the threatened Baluchistan black bear. To address these gaps and improve conservation efforts, we recommend increasing applied research both inside and outside protected areas and employing updated methodologies like camera trapping, remote sensing, ecological modelling and genetic analysis. It is imperative to conduct studies across the entire distribution range, especially in understudied areas like southern Khyber Pakhtunkhwa and Balochistan, to ensure the long-term conservation of the Asiatic black bear across its entire distribution.

Target Mining in Insect Genomes: Omics-Guided Innovations for Smart Pesticides - Muhammad Faizan Khurram; Maryam Tahira; Abdul Rauf; Burhan Khalid; Muhammad Ikram (Journal of Crop Health, 2025)

Arsenic speciation using HPLC–ICP–MS in white and brown rice and health risk assessment - Raneesha Navaretnam; Ahmad Zaharin Aris; Muhammad Faizan A. Shukor; Mohd Nor Faiz Norrrahim; Victor Feizal Knight; Teen Teen Chin; Noorain Mohd Isa; Ley Juen Looi (Environmental Geochemistry and Health, 2025)

Foliar Application of Silicon Alleviates Drought Stress in Chickpea (Cicer arietinum L.) by Improving Growth, Photosynthetic and Antioxidant Metabolism - Muhammad Faizan Ali; Mukhtar Ahmed; Laiba Mukhtar; Nadir Ali; Ghulam Qadir; Rifat Hayat; Shakeel Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Genetic Variability Among Isolates of Curvularia lunata and Exserohilum rostratum Causing Brown Leaf Spot of Rice from Pakistan - Muhammad Faizan Anwar Khan; Abid Riaz; Rafia Ahsan; Ishaq Ahmad; Saif Ullah; Ahmed Raza; Muhammad Zakria (Current Microbiology, 2025)

Response of Potato Yield, Soil Organic Matter, Microbial Properties, and Pesticide Residues to Different Cropping Systems and Nutrient Management in North Pakistan - Nanak khan; Zammurad Iqbal Ahmed; Mukhtar Ahmed; Muhammad Faizan Ali; Ghulam Jilani (Potato Research, 2025)

Synergistic Application of Biochar and Bio-Organic Phosphate Enhances Drought Tolerance in Maize by Modulating Antioxidant Defense and Reducing Oxidative Stress - Ghulam Sarwar; Zainab Zahra; Tauseef Anwar; Huma Qureshi; Faizan Khalid; Muhammad Waqar Hassan; Muhammad Younus; Muhammad Sajid-ur-Rehman; Huma Rao; Faisal Shahzad; Wajid Zaman; Mansour Shrahili; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Nanoparticle-Mediated Phytohormone Interplay: Advancing Plant Resilience to Abiotic Stresses - Faizan Khalid; Yumna Rasheed; Humaira Ashraf; Kanza Asif; Muhammad Faisal Maqsood; Muhammad Shahbaz; Usman Zulfiqar; Fozia Farhat; Saher Nawaz; Muhammad Ahmad (Journal of Crop Health, 2025)

Immunoprotective potential of egg yolk antibodies (IgYs) in controlling necrotic enteritis in broiler chickens - Zain Ul Abadeen; Muhammad Tariq Javed; Tariq Jamil; Syed Muhammad Faizan (Veterinary Immunology and Immunopathology, 2025)

The Role of Pseudomonas aeruginosa, Burkholderia phytofirmans and Acinetobacter junii in Phytoremediation of Crude Oil and Stimulation of Physio-Biochemical Activities of Wheat - Ume Ummara; Farrukh Jaleel; Faizan Ahmed; Omar Mahmoud Al-Zoubi; Sehrish Iqbal; Nargis Naz; Muhammad Afzal; Suliman Mohammed Suliman Alghanem; Modhi O. Alotaibi (Journal of Soil Science and Plant Nutrition, 2025)

T-2 mycotoxin: From occurrence and toxicokinetics to recent advances in aptasensor-based detection strategies and future perspectives for enhanced food safety - Ali Raza; Sobia Niazi; Muhammad Shoaib; Imran Mahmood Khan; Faizan Ul Haq; Khubaib Ali; Ibrahim Khan; Yin Zhang; Zhouping Wang (Trends in Food Science & Technology, 2025)

A novel eco-friendly electrochemical fabrication of magnetic bimetallic-organic framework sensors for ultrasensitive detection of dual miRNAs - Muhammad Faizan; Chi-Hsien Liu; Wei-Chi Wu (Journal of Environmental Chemical Engineering, 2025)

Bio-templating approach and DFT study of ZrMo@KIT-6 catalyst for the conversion of deep fried oil into sustainable biodiesel production - Muhammad Noman; Muhammad Farooq; Anita Ramli; Ghazala Abid; Fouzia Perveen; Dur Muhammad; Rida Ihsan; Faizan Jamil; Ali Raza Ayub; Noor Saeed khattak; Ata Ur Rahman (Fuel, 2025)

A Novel Optimized Vibration-based Energy Harvester for Leak Detection in Wall-mounted Water Pipelines - Muhammad Faizan Mysorewala; Mati-Ur-Rasool Ashraf Virk; Mujahid Naqeebuddin Syed; Abdul-Wahid Saif; Lahouari Cheded; Saifullah Shafiq; Karim Sattar (Water Resources Management, 2025)

Effect of plastic fibers on OPC-based concrete in circular economy - Shehroze Ali; Suliman Khan; Muhammad Imran; Faizan Ali; Mohsin Nawaz (Innovative Infrastructure Solutions, 2025)

Residual effects of biochar and nano-modified biochar on growth and physiology under saline environment in two different genotype of Oryza sativa L. - Haider Sultan; Hafiz Muhammad Mazhar Abbas; Mohammad Faizan; Abolghassem Emamverdian; Asad Shah; Saraj Bahadur; Yusheng Li; Mohammad Nauman Khan; Lixiao Nie (Journal of Environmental Management, 2025)

Revolutionizing Fingerprint Detection: Ce3+ Doped SiO2-Zr2O3:Sr2+ Nanocomposites with Enhanced Luminescence and Selectivity - Momna Qayyum; Sammia Shahid; Sana Mansoor; Muhammad Faizan; Mohsin Javed; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Salman Aloufi (Journal of Fluorescence, 2024)
Even though fingerprints remain one of the most reliable methods of identification, they are often lost during the recovery process. Accurate fingerprint recognition depends on the contrast between the ridges and substrate. On tough surfaces, such as glossy, colorful, and patterned materials, the contrast is harder to establish. Photoluminescent materials play a crucial role in forensic investigations as they enable the development of procedures that enhance image quality and increase the accuracy of findings from security institutions. Due to the strong emission in the red area at 620 nm, the use of trivalent Rare Earth ions (RE 3+ ) doped materials in this work is notable. Because of the unique properties and abundance of cerium, luminous materials based on SiO 2 -Zr 2 O 3 : Ce 3+ , Sr 2+ prepared via sol-gel technique present a more practical alternative for use in criminal investigations compared to current photonic materials. The sample was further co-doped with synthetic (Safranin-O and crystal violet) as well as organic (curcumin and lycopene) photoluminescent dyes. The nanocomposites were examined using X-ray diffraction analysis (XRD), energy-dispersive X-ray analysis (EDX), dynamic light scattering (DLS), scanning electron microscopy (SEM), and photoluminescence spectroscopy (PL). In conclusion, this work highlights the qualities critical to obtaining higher-resolution latent fingerprint images for potential forensic applications.

CRISPR-Cas9 based molecular breeding in crop plants: a review - Muhammad Ikram; Abdul Rauf; Muhammad Junaid Rao; Muhammad Faizan Khurram Maqsood; Muhammad Zeeshan Mola Bakhsh; Maaz Ullah; Maria Batool; Muhammad Mehran; Maryam Tahira (Molecular Biology Reports, 2024)

Plant Biostimulants: Mechanisms and Applications for Enhancing Plant Resilience to Abiotic Stresses - Faizan Khalid; Yumna Rasheed; Kanza Asif; Humaira Ashraf; Muhammad Faisal Maqsood; Muhammad Shahbaz; Usman Zulfiqar; Rehana Sardar; Fasih Ullah Haider (Journal of Soil Science and Plant Nutrition, 2024)

Distribution, diel activity patterns and human-bear interactions of the Himalayan brown bear (Ursus arctos isabellinus) in the Deosai National Park, Pakistan - Tosif Fida; Faizan Ahmad; Luciano Bosso; Neeha Ali; Shams Ud Din; Muhammad Kabir (Mammal Research, 2024)

Impact of different range areas on behavior, welfare, and performance of Naked Neck chickens - Saba Zahid; Muhammad Usman; Hafiz Muhammad Ishaq; Muhammad Faizan Haider; Mian Mubashar Saleem; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad; Tarek Amin Ebeid (Tropical Animal Health and Production, 2024)

Pharmacogenetic study of CES1 gene and enalapril efficacy - Misbah Hussain; Sehrish Basheer; Adila Khalil; Qurat Ul Ain Haider; Hafsa Saeed; Muhammad Faizan (Journal of Applied Genetics, 2024)

Correction to: Application of species distribution models to estimate and manage the Asiatic black bear (Ursus thibetanus) habitat in the Hindu Kush Mountains, Pakistan - Muhammad Rehan; Ammar Hassan; Shah Zeb; Sami Ullah; Faizan Ahmad; Eve Bohnett; Luciano Bosso; Tosif Fida; Muhammad Kabir (European Journal of Wildlife Research, 2024)

Enhancing Plant Stress Resilience with Osmolytes and Nanoparticles - Yumna Rasheed; Faizan Khalid; Humaira Ashraf; Kanza Asif; Muhammad Faisal Maqsood; Nargis Naz; Muhammad Shahbaz; Usman Zulfiqar; Qasim Ali; Shamsa Rana (Journal of Soil Science and Plant Nutrition, 2024)

Application of species distribution models to estimate and manage the Asiatic black bear (Ursus thibetanus) habitat in the Hindu Kush Mountains, Pakistan - Muhammad Rehan; Ammar Hassan; Shah Zeb; Sami Ullah; Faizan Ahmad; Eve Bohnett; Luciano Bosso; Tosif Fida; Muhammad Kabir (European Journal of Wildlife Research, 2024)

Assessing Asiatic black bear (Ursus thibetanus) temporal overlap and co-occurrence with sympatric species in the temperate zone of the Hindu Raj Mountain range - Faizan Ahmad; Muhammad Rehan; Eve Bohnett; Ammar Hassan; Sami Ullah; Shah Zeb; Hammad Ali Mian; Muhammad Kabir (European Journal of Wildlife Research, 2024)

Transgenic expression of artificial microRNA targeting soybean mosaic virus P1 gene confers virus resistance in plant - Muhammad Faizan Latif; Jingquan Tan; Wang Zhang; Wenxuan Yang; Tinghui Zhuang; Wenlong Lu; Yanglin Qiu; Xinying Du; Xinjian Zhuang; Tong Zhou; Jiban K. Kundu; Jinlong Yin; et al. (Transgenic Research, 2024)

Assessment of water quality using entropy-weighted quality index, statistical methods and electrical resistivity tomography, Moti village, northern Pakistan - Umair Bin Nisar; Wajeeh ur Rehman; Saher Saleem; Kashif Taufail; Faizan ur Rehman; Muhammad Farooq; Siddique Akhtar Ehsan (Journal of Contaminant Hydrology, 2024)

Nutrient and mycoremediation of a global menace ‘arsenic’: exploring the prospects of phosphorus and Serendipita indica-based mitigation strategies in rice and other crops - Shafaque Sehar; Muhammad Faheem Adil; Syed Muhammad Hassan Askri; Elvis Dennis; Mohammad Faizan; Ping Zhao; Fanrui Zhou; Imran Haider Shamsi (Plant Cell Reports, 2024)

Synergistic effect of Paclobutrazol and silver nanoparticles (AgNPs) control the pod shattering in canola (Brassica napus L.) via physiological interferences: a mechanistic overview - Habib Ali; Imran Mahmood; Ghulam Qadir; Naveed Iqbal Raja; Fozia Abasi; Mukhtar Ahmed; Muhammad Faizan Ali; Husnain Jawad; Jarosław Proćków (Acta Physiologiae Plantarum, 2024)

Spectrophotometric, microscopic, crystallographic and X-ray based optimization and biological applications of Olea paniculata leaf extract mediated silver nanoparticles - Muhammad Faran Akhtar; Muhammad Irshad; Shaukat Ali; Muhammad Summer; Muhammad Jawad; Muhammad Faizan Akhter; Muhammad Adeel Farooq; Ghulam Asghar (South African Journal of Botany, 2024)

Biochar and nano biochar: Enhancing salt resilience in plants and soil while mitigating greenhouse gas emissions: A comprehensive review - Haider Sultan; Yusheng Li; Waqas Ahmed; Mu yixue; Asad Shah; Mohammad Faizan; Aqeel Ahmad; Hafiz Muhammad Mazhar Abbas; Lixiao Nie; Mohammad Nauman Khan (Journal of Environmental Management, 2024)

Development and Characterization of Glimepiride-Loaded Polymeric Nanoparticles: Formulation Design and Evaluation - Zaiba Irfan; Muhammad Imran Khan; Muhammad Farhan Sohail; Muhammad Furqan Akhtar; Muhammad Naeem Qaisar; Muhammad Kashif Javed; Fareeha Anwar; Badarqa-tul-Ayesha; Majid Anwar; Aslam Khan; Faizan Akram (Journal of Pharmaceutical Innovation, 2024)

CRISPR/Cas9-based genome editing: A revolutionary approach for crop improvement and global food security - Ghulam Muha-Ud-Din; Faizan Ali; Akhtar Hameed; Syed Atif Hasan Naqvi; Mir Muhammad Nizamani; Muhammad Jabran; Sohaib Sarfraz; Wang Yong (Physiological and Molecular Plant Pathology, 2024)

Nutraceutical and Health-Promoting Potential of Lactoferrin, an Iron-Binding Protein in Human and Animal: Current Knowledge - Muhammad Faizan Ashraf; Dawood Zubair; Muhammad Noaman Bashir; Mahmoud Alagawany; Shabbir Ahmed; Qurban Ali Shah; Jameel Ahmed Buzdar; Muhammad Asif Arain (Biological Trace Element Research, 2024)

Growth of tunable Au-BaO@TiO2/CdS heterostructures: Acceleration of hydrogen evolution from water splitting - Mamoona Sabir; Khezina Rafiq; Muhammad Zeeshan Abid; Ujala Quyyum; Syed Shoaib Ahmad Shah; Muhammad Faizan; Abdul Rauf; Shahid Iqbal; Ejaz Hussain (Fuel, 2023)

Evaluation of ionospheric and solar proxy indices for IRI-Plas 2020 model over Pakistan and Japan during different solar activity epochs - Faizan Abbas; Muhammad Ayyaz Ameen (Advances in Space Research, 2023)

Evaluating the determinants of wildlife tolerance in the Kavango-Zambezi Transfrontier Conservation Area in Zimbabwe - Muhammad Faizan Usman; Sebastien Le Bel; Patrice Grimaud; Martin Reinhardt Nielsen (Journal for Nature Conservation, 2023)

Plasmonic titanium nitride based ammonia synthesis by Photo-electrocatalytic reduction of nitrogen - Manpreet Kaur; Muhammad Faizan; Hua Song (Chemical Engineering Journal, 2023)

Nano priming for boosting growth and resilience in crops under abiotic stresses - Faizan Khalid; Kanza Asif; Yumna Rasheed; Humaira Ashraf; Muhammad Faisal Maqsood; Shamsa Rana; Usman Zulfiqar; Nargis Naz; Muhammad Shahbaz; Rehana Sardar; Zunaira Riaz (Biocatalysis and Agricultural Biotechnology, 2023)

A game theory approach to land acquisition conflicts in Pakistan - Ahsan Shafi; Zhanqi Wang; Muhsan Ehsan; Faizan Ahmed Riaz; Muhammad Rashid Ali; Feng Xu (Land Use Policy, 2023)

Evidence and Molecular Characterization of Multidrug Resistant Staphylococcus aureus Isolated From Equines in Pakistan - Farwa Anwaar; Muhammad Ijaz; Hamza Rasheed; Syed Faizan Ali Shah; Syed Ali Raza Haider; Muhammad Jawad Sabir (Journal of Equine Veterinary Science, 2023)

Critical review on catalytic biomass gasification: State-of-Art progress, technical challenges, and perspectives in future development - Muhammad Faizan; Hua Song (Journal of Cleaner Production, 2023)

Occurrence and risk evaluation of endocrine-disrupting chemicals in wastewater and surface water of Lahore, Pakistan - Muhammad Ashfaq; Yan Li; Muhammad Zubair; Muhammad Saif Ur Rehman; Sajjad Hussain Sumrra; Muhammad Faizan Nazar; Ghulam Mustafa; Muhammad Tahir Fazal; Humayun Ashraf; Qian Sun (Environmental Geochemistry and Health, 2023)

Unveiling the genomic potential of a novel thermostable glycoside hydrolases producing Neobacillus sedimentimangrovi UE25 - Uroosa Ejaz; Faizan Saleem; Rozina Rashid; Khwaja Ali Hasan; Muhammad Noman Syed; Muhammad Sohail (Antonie van Leeuwenhoek, 2023)

First report of clover yellow vein virus infecting Pisum sativum in China - Jinlong Yin; Jingquan Tan; Sha Luo; Xin Hong; Yuanming Zhang; Yangling Qiu; Muhammad Faizan Latif; Kai Xu (Journal of Plant Pathology, 2023)

Phytotoxic responses of wheat to an imidazolium based ionic liquid in absence and presence of biochar - Taza Gul; Muhammad Mudasar Aslam; Amir Sada Khan; Tahir Iqbal; Faizan Ullah; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Muhammad Saeed Akhtar (Chemosphere, 2023)

Variation of ionosonde f o E and its comparison with IRI-2016 & a local model over Pakistan longitude sector during solar cycle 22 - Muhammad Ayyaz Ameen; Aisha Ghulam Muhammad; Faizan Abbas; Afnan Tahir; Madeeha Talha (Advances in Space Research, 2023)

Bioplastics from waste biomass of marine and poultry industries - Amna Arif; Farrukh Azeem; Ijaz Rasul; Muhammad Hussnain Siddique; Muhammad Zubair; Faizan Muneer; Warda Zaheer; Habibullah Nadeem (Journal of Biosciences, 2023)

Evaluation of single-phase net metering to meet renewable energy targets: A case study from Pakistan - Muhammad Usman Tahir; Kiran Siraj; Syed Faizan Ali Shah; Naveed Arshad (Energy Policy, 2023)

How ICT and globalization interact with the environment: a case of the Chinese economy - Munaza Bibi; Muhammad Kamran Khan; Muhammad Mutasim Billah Tufail; Danish Iqbal Godil; Rimsha Usman; Muhammad Faizan (Environmental Science and Pollution Research, 2023)

Natural polysaccharide-based biodegradable polymeric platforms for transdermal drug delivery system: a critical analysis - Sobia Noreen; Jin-Xiang Ma; Muhammad Saeed; Fahad Pervaiz; Muhammad Farhan Hanif; Bilal Ahmed; Muhammad Irshad Farooq; Faizan Akram; Muhammad Safdar; Asadullah Madni; Muhammad Naveed; Li Chang-Xing (Drug Delivery and Translational Research, 2022)

Characterization of functional genes GS3 and GW2 and their effect on the grain size of various landraces of rice (Oryza sativa) - Haroon Rasheed; Sajid Fiaz; Muhammad Abid Khan; Sultan Mehmood; Faizan Ullah; Sumbul Saeed; Shahid Ullah Khan; Tabassam Yaseen; Reem M. Hussain; Abdul Qayyum (Molecular Biology Reports, 2022)

New organosulfur metallic compounds as potent drugs: synthesis, molecular modeling, spectral, antimicrobial, drug likeness and DFT analysis - Abrar Ul Hassan; Sajjad Hussain Sumrra; Muhammad Nadeem Zafar; Muhammad Faizan Nazar; Ehsan Ullah Mughal; Muhammad Naveed Zafar; Mazhar Iqbal (Molecular Diversity, 2022)

Paleostress inversion and outcrop fracture analysis of the brittle deformation along Main Boundary Thrust (MBT), NW Himalaya, Pakistan - Naveed Ahsan; Hassan Mehmood; Muhammad Armaghan Faisal Miraj; Iqra Bano; Abdul Qayyum; Rana Faizan Saleem (Journal of Earth System Science, 2021)

Economic assessment of prospective shale gas play in Pakistan using discounted cashflow model - Faizan Ali; Muhammad Arqam Khan; Naeem ul Hussain Dahraj; Musab Usman; Laiba Sajid Cheema (Arabian Journal of Geosciences, 2021)

Isolation and identification of low-density polyethylene degrading novel bacterial strains - Habibullah Nadeem; Khush Bakhat Alia; Faizan Muneer; Ijaz Rasul; Muhammad Hussnain Siddique; Farrukh Azeem; Muhammad Zubair (Archives of Microbiology, 2021)

Data-Driven Modeling Approach to Predict the Recovery Performance of Low-Salinity Waterfloods - Shams Kalam; Rizwan Ahmed Khan; Shahnawaz Khan; Muhammad Faizan; Muhammad Amin; Rameez Ajaib; Sidqi A. Abu-Khamsin (Natural Resources Research, 2021)

Co-culturing corncob-immobilized yeasts on orange peels for the production of pectinase - Faizan Qadir; Uroosa Ejaz; Muhammad Sohail (Biotechnology Letters, 2020)

Microbial l-asparaginase: purification, characterization and applications - Faizan Muneer; Muhammad Hussnain Siddique; Farrukh Azeem; Ijaz Rasul; Saima Muzammil; Muhammad Zubair; Muhammad Afzal; Habibullah Nadeem (Archives of Microbiology, 2020)

First report of Geotrichum candidum causing postharvest sour rot of carrot in Punjab, Pakistan - Akhtar Hameed; Muhammad Waqar Alam; Abdul Rehman; Khalid Naveed; Muhammad Atiq; Nasir Ahmed Rajput; Sohaib Sarfraz; Nadia Liaqat; Faizan Ahmad Tahir (Journal of Plant Pathology, 2019)

A Multiscale Approach to Leak Detection and Localization in Water Pipeline Network - Najam us Saqib; Muhammad Faizan Mysorewala; Lahouari Cheded (Water Resources Management, 2017)

Development of a Polygonum minus cell suspension culture system and analysis of secondary metabolites enhanced by elicitation - Muhammad Faizan A. Shukor; Ismanizan Ismail; Zamri Zainal; Normah Mohd Noor (Acta Physiologiae Plantarum, 2013)

Synthesis of Novel Fluorescent Cyclohexenone Derivatives and their Partitioning Study in Ionic Micellar Media - Amir Badshah; Saleem Nawaz; Muhammad Faizan Nazar; Syed Sakhawat Shah; Aurangzeb Hasan (Journal of Fluorescence, 2010)

Microemulsion System with Improved Loading of Piroxicam: A Study of Microstructure - Muhammad Faizan Nazar; Asad Muhammad Khan; Syed Sakhawat Shah (AAPS PharmSciTech, 2009)